Biocompatibility testing of novel starch-based materials with potential application in orthopaedic surgery: a preliminary study - Mendes, Sandra C. (2001)
This paper describes an extensive biocompatibility evaluation of biodegradable starch-based materials aimed at orthopaedic applications as temporary bone replacement fixation implants. For that purpose, a polymer (starch/ethylene vinyl alcohol blend, SEVA-C) and a composite of SEVA-C reinforced with hydroxyapatite (HA) particles, were evaluated in both in vitro and in vivo assays. For the in vitro analysis cell culture methods were used. The in vivo tissue reactions were evaluated in an intramuscular and intracortical bone implantation model on goats, using light and scanning electron microscopy. A computerized image analysis system was used to obtain histomorphometric data regarding bone contact and remodelling after 6 and 12 weeks of implantation. In both in vitro and in vivo models, the SEVA-C-based materials did not induce adverse reactions, which in addition to their bone-matching mechanical properties makes them promising materials for bone replacement fixation.